ASXLs binding to the PHD2/3 fingers of MLL4 provides a mechanism for the recruitment of BAP1 to active enhancers - Zhang, Yi; Xie, Guojia; Lee, Ji-Eun; Zandian, Mohamad; Sudarshan, Deepthi; Estavoyer, Benjamin; Benz, Caroline; Viita, Tiina; Asgaritarghi, Golareh; Lachance, Catherine; Messmer, Clémence; Simonetti, Leandro; et al. (Nature communications, 2024)
The human methyltransferase and transcriptional coactivator MLL4 and its paralog MLL3 are frequently mutated in cancer. MLL4 and MLL3 monomethylate histone H3K4 and contain a set of uncharacterized PHD fingers. Here, we report a novel function of the PHD2 and PHD3 (PHD2/3) fingers of MLL4 and MLL3 that bind to ASXL2, a component of the Polycomb repressive H2AK119 deubiquitinase (PR-DUB) complex. The structure of MLL4 PHD2/3 in complex with the MLL-binding helix (MBH) of ASXL2 and mutational analyses reveal the molecular mechanism which is conserved in homologous ASXL1 and ASXL3. The native interaction of the Trithorax MLL3/4 complexes with the PR-DUB complex in vivo depends solely on MBH of ASXL1/2, coupling the two histone modifying activities. ChIP-seq analysis in embryonic stem cells demonstrates that MBH of ASXL1/2 is required for the deubiquitinase BAP1 recruitment to MLL4-bound active enhancers. Our findings suggest an ASXL1/2-dependent functional link between the MLL3/4 and PR-DUB complexes. Human methyltransferase MLL4 mediates embryonic development and is dysregulated in diseases. Zhang et al. found that binding of PHD fingers of MLL4 to ASXL1/2 is required for recruitment of the deubiquitinase BAP1 to MLL4-bound active enhancers in vitro.